Impact of dumpsite compost on heavy metal accumulation in some cultivated plants - Basma T. Abd-Elhalim; Mathew Gideon; Kuzmin Anton; Mercy O. Boyi (BMC Research Notes)
Abstract The study examines the concentrations of heavy metals in agricultural soil, compost from landfills, maize plants, and spinach crops. The results show that compost from landfills had levels exceeding EU requirements for Cd, Cu, Ni, Pb, and Zn. However, agricultural soil contained trace amounts of heavy metals. The order of metal absorption by plants was Cd > Pb > Cu > Ni > Cr > Zn > Fe > Mn. This highlights potential health risks associated with consuming crops grown in compost or soil tainted with heavy metals.